Hubungan Kemandirian Belajar dengan Hasil Belajar pada Matakuliah Matematika-II - Siregar, Nurdiana; Siregar, Nurkhairunnisa (IAIN PADANGSIDIMPUAN, 2019)
The purpose of this study was to look at the relation between self-regulated learning and learning outcomes of PGMI study program students at UIN North Sumatra. This type of research is quantitative research using the correlational method. 42 students of PGMI study program were used as samples in this study. Data collection was done using a questionnaire and a list of grades Mathematics-II students (Geometry and Measurement). Based on the results of the pearson correlation test output obtained that there is a significant relation of self-regulated learning with student learning outcomes in Mathematics-II subjects. Furthermore, to see the strength or closeness of the correlation between the two variables can be taken a decision from the Pearson Correlation value of 0.793 is in the interpretation of the r value is strongly correlated, then the closeness or strength of the relationship between the two variables is categorized strong. Thus there is a strong positive correlation between self-regulated learning variables with learning outcomes of Mathematics-II subjects. Such a relationship can be interpreted that the higher the level of learning independence, the higher the achievement of student learning outcomes tends to be.